Composite additive and method for improving comprehensive performance of iron ore oxidized pellets with high alkali metal content
By using a composite additive of steel slag, blast furnace slag and bentonite in iron ore pellets with high alkali metal content, the liquid phase generation and distribution are regulated, which solves the problems of low pellet strength and high reduction expansion, realizes high-strength and low-expansion iron ore pellets, and improves smelting efficiency and production stability.
Patent Information
- Application Number
- CN202511134132.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2045-08-14
AI Technical Summary
In the existing technology, when using high-alkali metal content iron concentrate and sodium-based bentonite to prepare pellets, the pellets have low strength and high reduction expansion, which leads to abnormal blast furnace operation and affects smelting efficiency and production stability.
A composite additive composed of steel slag, blast furnace slag and bentonite is used to form a stable liquid phase by regulating the SiO2 and CaO contents, inhibiting the migration of alkali metal ions, reducing the amount of alkali metal ferrite generated, improving the reduction expansion behavior of the pellets, and enhancing the structural density.
Significantly reduce the reduction expansion of pellets, improve the compressive strength of finished pellets, and achieve high-strength and low-expansion iron ore pellets with high resource utilization and environmental friendliness.
Smart Images

Figure CN120776111A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a kind of pellet composite additives, in particular to a kind of composite additive for improving the comprehensive performance of high alkali content iron ore oxidized pellet, and further relates to the method of composite additive for preparing high alkali content iron ore oxidized pellet, belongs to the technical field of iron ore pellet production. BACKGROUND
[0002] With the development of steel industry towards high efficiency, green direction, pellet as a kind of excellent metallurgical performance high quality blast furnace burden, has been widely used in blast furnace ironmaking system. In order to further reduce the energy consumption of blast furnace ironmaking, the increase of pellet proportion in burden, has become one of the main directions of future blast furnace ironmaking. Therefore, the demand of pellet is increasing.
[0003] In addition, under the background of high quality iron ore resources is increasingly tight, the complex gangue composition of iron ore concentrate in the high proportion of application in pellet has become one of the development direction of pellet. On this basis, high alkali content of iron ore resources is widely used in pellet preparation field. At the same time, because sodium bentonite as balling binder is cheap, leading to the application in pellet is more widely. Therefore, when using high alkali content of iron ore concentrate and sodium bentonite to prepare pellet, the alkali content in the prepared pellet increases significantly. Research shows that alkali in pellet reacts with Fe2O3 and other iron oxides to generate alkali containing ferrite during oxidation process. The generation of this kind of alkali ferrite leads to the rapid growth of local metallic iron in pellet during subsequent reduction process. Therefore, it causes the vicious volume expansion and even the powdering and crushing phenomenon of pellet. When entering the blast furnace, this kind of pellet expansion will significantly reduce the permeability of material column, destroy the permeability of burden structure, lead to abnormal operation of blast furnace, such as suspension, collapse, hanging furnace and other problems, which seriously restricts the smelting efficiency and production stability. Chinese patent (CN106367584A) discloses a method for preparing oxidized pellet using high alkali iron ore concentrate, but its utilization rate of high alkali iron ore concentrate is less than 50%, which needs to be mixed with a large amount of low alkali iron ore concentrate, and it needs to use magnesium additive to reduce the expansion rate of oxidized pellet and improve the metallurgical performance, and the compressive strength of finished pellet is relatively low (more than 2000N·P -1 ), the expansion rate is higher (18.9%). SUMMARY
[0004] In view of the technical problems of low strength and high reduction expansion of the pellets prepared by using high-alkali iron concentrate and sodium-based bentonite in the prior art, a first object of the present application is to provide a composite additive for improving the comprehensive performance of high-alkali iron ore oxidized pellets, which can increase the liquid phase content in the pellets, optimize the distribution of alkali metals in the pellets during the oxidizing roasting process, avoid the formation of alkali metal-containing ferrite, and effectively inhibit the malignant expansion of the pellets caused by the rapid growth of local metallic iron in the subsequent reduction process, so as to obtain high-strength and low-expansion iron ore pellets.
[0005] A second object of the present application is to provide a preparation method of high-alkali iron ore oxidized pellets, which adds a composite additive composed of steel slag, blast furnace slag and bentonite, etc. in the balling process of high-alkali iron concentrate, uses SiO2 and CaO contained in the composite additive to regulate the liquid phase formed during the oxidizing roasting process of the pellets, uses the liquid phase to inhibit the migration of alkali metal ions into hematite, reduces the generation amount of alkali metal-containing ferrite, and further improves the reduction expansion behavior of the pellets, and at the same time uses the liquid phase to fill the pores and enhance the structural compactness, thereby improving the compressive strength of the finished pellets.
[0006] In order to achieve the above technical objects, the present application provides a composite additive for improving the comprehensive performance of high-alkali iron ore oxidized pellets, which is composed of steel slag, blast furnace slag and bentonite in a mass percentage of 25-65%:20-70%:5-15%; the mass content of SiO2 and CaO in the blast furnace slag is 30-40% and 35-45%, respectively, and the total mass content of other impurities is not higher than 25%; the mass content of SiO2 and CaO in the steel slag is 10-20% and 40-50%, respectively.
[0007] The composite additive of the present application is mainly composed of steel slag, blast furnace slag and bentonite. The blast furnace slag has a high SiO2 content and a low CaO content, and the high SiO2 content helps to increase the liquid phase content in the pellets. However, the high SiO2 content leads to a high melting point of the generated liquid phase. The steel slag is rich in CaO and has a relatively low SiO2 content. Therefore, the use of the steel slag in combination with the blast furnace slag can optimize the melting point of the liquid phase. Thus, the present application combines the steel slag and the blast furnace slag to effectively adjust the SiO2 and CaO contents in the pellet raw materials, so as to control the liquid phase content and the liquid phase melting point formed in the oxidizing roasting process of the pellets. The liquid phase can stabilize the distribution of alkali metal ions, and has a capturing and stabilizing effect on the alkali metal ions, thereby inhibiting the migration of the alkali metal ions into the hematite, effectively reducing the generation amount of alkali metal-containing ferrite, and improving the reduction swelling behavior of the pellets. The generated liquid phase has good wetting performance and fluidity, can fill the internal pores of the pellets and enhance the structural compactness, and thus improves the compressive strength of the finished pellets. The bentonite is further introduced into the composite additive, which mainly serves to improve the bonding performance of the composite additive and improve the matching between the composite additive and the high-alkali-content iron concentrate, thereby improving the pelletizability of the high-alkali-content iron concentrate.
[0008] By adjusting the ratio of the steel slag, the blast furnace slag and the bentonite within a suitable range, the present application can realize the relative balance of the liquid phase components, avoid the problem of reducing the liquid phase content due to the excessively high melting point of the liquid phase, and improve the wetting performance and fluidity of the liquid phase, and effectively optimize the distribution of the liquid phase in the pellets. The liquid phase in the pellets is mainly controlled by SiO2 and CaO, and the mass contents of SiO2 and CaO are preferably controlled within the ranges of 2.5-6.0% and 1.0-5.5%, respectively.
[0009] The blast furnace slag and the steel slag used in the present application mainly contain SiO2 and CaO. The SiO2 and CaO components are beneficial to form a stable liquid phase in the oxidizing roasting process of the pellets, thereby effectively wrapping and fixing the alkali metal ions and inhibiting the migration of the alkali metal ions into the hematite, so as to reduce the generation amount of alkali metal-containing ferrite and improve the reduction swelling behavior of the pellets. In addition, the SiO2 content in the blast furnace slag is higher than that in the steel slag, and the CaO content in the blast furnace slag is lower than that in the steel slag. Therefore, the appropriate combination of the two can control the mass contents of SiO2 and CaO within a wide range.
[0010] The present application further provides a preparation method of high-alkali-content iron ore oxidized pellets. The method is to mix the composite additive after ball milling and activation with high-alkali-content iron concentrate to form green balls, and then dry, preheat and roast the green balls in sequence to obtain the pellets.
[0011] The key of the application in preparing high alkali metal content iron ore oxidized pellets is that a composite additive composed of steel slag, blast furnace slag and bentonite etc. is added, the composite additive has the characteristics of high CaO and SiO2 content, and in the production process of high alkali metal content iron concentrate pellets, the composite additive has the characteristics of small adding amount and large liquid phase generation amount, and the liquid phase generation amount, liquid phase melting point and uniform distribution of liquid phase in the pellets are adjusted by CaO and SiO2 etc., the migration of alkali metal ions is inhibited by the liquid phase, the pellet reduction expansion is significantly reduced, and meanwhile, the filling effect of the liquid phase on the internal pores and the structure densification are utilized, so that the pellets with high strength can be obtained. In addition, the composite additive introduces a small amount of bentonite, so that the matching between the steel slag, the blast furnace slag and the high alkali metal content iron concentrate is good, and the balling performance is improved.
[0012] As a preferred scheme, the ball milling activation condition is that the rotation speed is 250-300 revolutions / min, the time is 30-60 min, and the mass ratio of ball to material is 2:1-5:1. Under the preferred ball milling activation condition, the mineral particles can be effectively broken, the specific surface area can be increased, and the reaction activity can be stimulated, so that the mineral particles are more easily involved in the liquid phase generation reaction in the roasting process. The generated liquid phase is beneficial to timely capturing and solidifying the migrated alkali metal in the oxidizing roasting stage, so as to play a key role in stabilizing the alkali metal and inhibiting the expansion.
[0013] As a preferred scheme, the particle size of the composite additive is controlled to meet that the mass ratio of the particle size of-38 μm is above 98%.
[0014] The application activates the components such as steel slag, blast furnace slag and bentonite by ball milling, the ball milling activation can reduce the reaction energy of the components, and meanwhile, the particle size of the components is refined, the contact efficiency between the components and the iron ore particles can be improved, the uniform formation of the liquid phase in the oxidizing roasting process can be promoted, the pores can be effectively filled, and the structure densification can be enhanced, so that the use amount of bentonite can be reduced and the compressive strength and reduction expansion of the finished pellets can be improved without affecting the green ball quality.
[0015] As a preferred scheme, the mass of the composite additive is 0.8-2.5% of the mass of the high alkali metal content iron concentrate. In the preferred use amount range of the composite additive, the liquid phase amount can be ensured to be sufficient to stabilize the alkali metal distribution, the TFe grade of the pellets can not be significantly reduced, and the compressive strength and reduction degree of the pellets can be improved.
[0016] As a preferred scheme, the mass content of the alkali metal in the high alkali metal content iron concentrate is 0.25-0.42%.
[0017] As a preferred scheme, the preheating condition is that the temperature is 920-950℃, and the time is 8-12 min. The preheating is performed in an air atmosphere.
[0018] As a preferred scheme, the roasting condition is that the temperature is 1250~1280℃, and the time is 15~20min.
[0019] Compared with the prior art, the technical scheme of the present application has the beneficial technical effects:
[0020] The composite additive of the present application is used for producing high-alkali-content iron concentrate pellets, has the characteristics of small addition amount and large liquid phase generation, and can obtain high-strength pellets while significantly reducing pellet reduction expansion.
[0021] The composite additive of the present application realizes the reuse of steel slag and blast furnace slag, reduces the environmental pollution caused by large-scale storage of the steel slag and the blast furnace slag, and realizes resource recycling.
[0022] The preparation method of the composite additive of the present application is simple in operation, short in process, wide in raw material source, and low in cost, and meets the industrial production. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 Figure (a) is the micro-morphology of the pellets of the comparative example 1 of the present application; and (b) is the micro-morphology of the pellets of the example 2 of the present application. DETAILED DESCRIPTION
[0024] The following examples are intended to further illustrate the present application, but not limit the protection scope of the claims of the present application.
[0025] In the following examples and comparative examples, the high-alkali-content iron concentrate, steel slag, blast furnace slag and bentonite used are commercially available raw materials.
[0026] The total mass content of K2O+Na2O in the high-alkali-content iron concentrate is 0.29%.
[0027] The content of SiO2 and CaO in the blast furnace slag is 40% and 35%, and the total content of other impurities is 25%.
[0028] The content of SiO2 and CaO in the steel slag is 13% and 45%.
[0029] Comparative Example 1:
[0030] The blast furnace slag, steel slag and bentonite were mixed in a ratio of 40:52:8 by weight, ball milled at a speed of 280 rpm for 30 min, and the ball-to-material mass ratio was 3:1. The ball milling was performed until the particle size met the requirement that the mass percentage of the -38 μm particle size was about 98.5%, and a composite additive was obtained. The composite additive and the high-alkali-content iron concentrate were mixed in a ratio of 0.4:99.6 by weight, and then pelletized. The preheating temperature was 940°C, and the oxidation roasting was performed for 10 min, followed by roasting at 1250°C for 20 min. The compressive strength of the finished pellet was 1600N, and the reduction swelling index was 89.87%.
[0031] Compared with Example 2, the process conditions were the same, the addition amount of the composite additive was reduced by about 1.0%, the strength of the pellet was reduced by 950N, and the reduction swelling index was increased by 73.42%. When the content of the composite additive is low, the amount of liquid phase generated in the pellet is low, which increases the porosity of the pellet and reduces the compressive strength of the pellet. In addition, when the amount of liquid phase is low, more alkali metal in the pellet generates alkali-containing ferrite, which promotes the growth of local metallic iron in the pellet during the subsequent reduction process, resulting in a higher reduction swelling of the pellet.
[0032] Comparative Example 2:
[0033] The blast furnace slag, steel slag and bentonite were mixed in a ratio of 45:45:10 by weight, and then the mixture was ball milled at a speed of 150 rpm for 15 min, and the ball-to-material mass ratio was 3:1. The ball milling was performed until the particle size met the requirement that the mass percentage of the -38 μm particle size was about 80%, and a composite additive was obtained. The composite additive and the high-alkali-content iron concentrate were mixed in a ratio of 1.0:99.0 by weight, and then pelletized. The preheating temperature was 950°C, and the oxidation roasting was performed for 15 min, followed by roasting at 1260°C for 20 min. The compressive strength of the finished pellet was 1600N, and the reduction swelling index was 56.95%.
[0034] Compared with Example 3, the raw material addition and roasting conditions were the same, the ball milling speed and time of the composite additive were reduced, the strength of the pellet was reduced by 763N, and the reduction swelling index was increased by 46.15%. When the particle size of the additive does not meet the requirement, it is difficult for the large particles of the additive to generate a suitable amount of liquid phase during the oxidation roasting process, which affects the distribution of alkali metal in the pellet. Therefore, the compressive strength of the pellet is reduced, and the reduction swelling is increased.
[0035] Comparative Example 3:
[0036] The blast furnace slag, steel slag and bentonite were mixed in a ratio of 15:75:10 by weight to obtain a mixture, and then the mixture was ball milled at a speed of 260 rpm for 40 min, with a ball-to-material mass ratio of 3:1, until the particle size met the requirement that the mass percentage of the -38 μm fraction was about 98.7%, to obtain a composite additive. The composite additive and the high-alkali-content iron concentrate were mixed in a ratio of 0.9:99.1 by weight, and then pelletized. Oxidation roasting was performed at a preheating temperature of 950 ℃ for 15 min, followed by roasting at 1260 ℃ for 20 min. The compressive strength of the finished pellet was 2200 N, and the reduction swelling index was 32.16%.
[0037] Compared with Example 1, the process conditions were the same, but the proportion of blast furnace slag in the additive was too low and the proportion of steel slag was too high, which led to a decrease in the content of introduced SiO2, thereby reducing the strength of the pellet by 700 N and increasing the reduction swelling index by 18.75%. Because the proportion of SiO2 in the additive was low, the liquid phase content in the pellet was low. Therefore, the compressive strength of the pellet was reduced and the reduction swelling was increased.
[0038] Comparative Example 4:
[0039] The blast furnace slag, steel slag and bentonite were mixed in a ratio of 35:55:10 by weight to obtain a mixture, and then the mixture was ball milled at a speed of 260 rpm for 40 min, with a ball-to-material mass ratio of 3:1, until the particle size met the requirement that the mass percentage of the -38 μm fraction was about 98.7%, to obtain a composite additive. The composite additive and the high-alkali-content iron concentrate were mixed in a ratio of 1.1:98.1 by weight, and then pelletized. Oxidation roasting was performed at a preheating temperature of 950 ℃ for 10 min, followed by roasting at 1150 ℃ for 20 min. The compressive strength of the finished pellet was 1689 N, and the reduction swelling index was 63.16%.
[0040] Compared with Example 4, the raw material addition and roasting conditions were the same, but the roasting temperature was reduced by 120 ℃, the strength of the pellet was reduced by 846 N, and the reduction swelling index was increased by 48.98%. When the roasting temperature was low, the additive failed to react with the gangue minerals in the iron concentrate to form a liquid phase, resulting in the additive mainly remaining in the pellet in the form of SiO2 and CaO. Therefore, the liquid phase was not sufficiently generated in the pellet, the alkali metals further reacted with the iron oxides to form ferrites, causing the strength of the pellet to decrease and the reduction swelling to increase.
[0041] Example 1:
[0042] The blast furnace slag, steel slag and bentonite are mixed in a ratio of 35:50:15 by weight to obtain a mixture, and then the mixture is ball milled at a speed of 260 rpm for 40 min, with a ball-to-material mass ratio of 3:1, until the particle size meets the requirement that the mass percentage of the -38 μm fraction is about 98.7%, to obtain a composite additive. The composite additive and high-alkali-content iron concentrate are mixed in a ratio of 0.9:99.1 by weight, and then pelletized. Oxidation roasting is performed at a preheating temperature of 950 ℃ for 15 min, and then roasting is performed at 1260 ℃ for 20 min. The compressive strength of the finished pellet is 2900 N, and the reduction swelling index is 13.41%.
[0043] Example 2:
[0044] The blast furnace slag, steel slag and bentonite are mixed in a ratio of 40:52:8 by weight to obtain a mixture, and then the mixture is ball milled at a speed of 280 rpm for 30 min, with a ball-to-material mass ratio of 3:1, until the particle size meets the requirement that the mass percentage of the -38 μm fraction is about 98.5%, to obtain a composite additive. The composite additive and high-alkali-content iron concentrate are mixed in a ratio of 1.4:98.6 by weight, and then pelletized. Oxidation roasting is performed at a preheating temperature of 940 ℃ for 10 min, and then roasting is performed at 1250 ℃ for 20 min. The compressive strength of the finished pellet is 2500 N, and the reduction swelling index is 16.45%.
[0045] Example 3:
[0046] The blast furnace slag, steel slag and bentonite are mixed in a ratio of 45:45:10 by weight to obtain a mixture, and then the mixture is ball milled at a speed of 270 rpm for 40 min, with a ball-to-material mass ratio of 3:1, until the particle size meets the requirement that the mass percentage of the -38 μm fraction is about 98.8%, to obtain a composite additive. The composite additive and high-alkali-content iron concentrate are mixed in a ratio of 1.0:99.0 by weight, and then pelletized. Oxidation roasting is performed at a preheating temperature of 950 ℃ for 15 min, and then roasting is performed at 1260 ℃ for 20 min. The compressive strength of the finished pellet is 2363 N, and the reduction swelling index is 10.80%.
[0047] Example 4:
[0048] The blast furnace slag, steel slag and bentonite are mixed in a ratio of 35:55:10 by weight to obtain a mixture, and then the mixture is ball milled at a speed of 260 r / min for 40 min with a ball-to-material mass ratio of 3:1, until the particle size reaches a mass percentage of about 98.7% in the -38 μm size fraction, to obtain a composite additive. The composite additive and the high-alkali-content iron concentrate are mixed in a ratio of 1.1:98.1 by weight, and then pelletized. Oxidation roasting is performed at a preheating temperature of 950 ℃ for 10 min, and then roasting is performed at 1270 ℃ for 20 min. The compressive strength of the finished pellet is 2535 N, and the reduction swelling index is 14.18%.
Claims
1. A composite additive for improving the comprehensive performance of iron ore oxidation pellets with high alkali metal content, characterized by: It is composed of steel slag, blast furnace slag and bentonite in the mass percentage of 25-65%:20-70%:5-15%; The mass content of SiO2 and CaO in the blast furnace slag is 30-40% and 35-45% respectively, and the total mass content of other impurities is not higher than 25%; The mass contents of SiO2 and CaO in the steel slag are 10%-20% and 40%-50% respectively.
2. A method for preparing iron ore oxide pellets with high alkali metal content, characterized in that: The composite additive according to claim 1 is activated by ball milling and then mixed with iron concentrate with high alkali metal content to form balls. The green balls obtained are dried, preheated and roasted in sequence to obtain pellets.
3. The method for preparing iron ore oxide pellets with high alkali metal content according to claim 2, characterized in that: The conditions for ball milling activation are: a rotation speed of 250-300 rpm, a time of 30-60 min, and a ball-to-material mass ratio of 2:1-5:
1.
4. The method for preparing iron ore oxide pellets with high alkali metal content according to claim 3, wherein: The ball milling activation is used to control the particle size of the composite additive to meet the mass ratio of the -38 μm particle size to be above 98%.
5. The method for preparing iron ore oxide pellets with high alkali metal content according to claim 2, 3 or 4, characterized in that: The mass of the composite additive is 0.8-2.5% of the mass of the high alkali metal content iron concentrate.
6. The method for preparing iron ore oxide pellets with high alkali metal content according to claim 5, characterized in that: The mass content of alkali metals in the high alkali metal content iron concentrate is 0.25-0.42%.
7. The method for preparing iron ore oxide pellets with high alkali metal content according to claim 2, characterized in that: The preheating conditions are: temperature of 920-950° C., and time of 8-12 minutes.
8. The method for preparing iron ore oxide pellets with high alkali metal content according to claim 2, characterized in that: The calcination conditions are: temperature of 1250-1280° C. and time of 15-20 min.
Citation Information
Patent Citations
Fluxed pellets for iron-making
CA1153894A
Pellets prepared from blast furnace slag iron fine powder as well as preparation method and application of pellets
CN104498708A
Production method of oxide pellets
CN106367584A
High-alkalinity pellet for blast furnace iron making and production method thereof
CN107488784A
Preparation method of iron ore pellets
CN110904334A